一种基于悬链线算法的激光点云电力线修补方法 (2025)
本发明涉及计算机技术领域，特别涉及一种基于悬链线算法的激光点云电力线修补方法。包括第一服务器，获取无人机采集的原始点云数据；对原始点云数据进行增强；还包括第二服务器，对增强数据切割；第二服务器执行方形网格分割算法，得到高点点云数据；第二服务器执行DBSCAN聚类算法得到似塔物集合数据，第二服务器执行DenseNet神经网络算法得到电塔点云数据；第二服务器执行yolov5神经网络算法得到电线点云数据；第二服务器执行欧式聚类算法得到单根电线点云数据；第二服务执行悬链线方程算法将电线缺失数据的补齐，模拟得到电力线点云数据。本发明节约了人力成本，解决了电力线点云缺失带来的误差问题，保障了电路隐患的及时检测，电网的安全运行。 The invention relates to the technical field of computers, in particular to a laser point cloud power line repairing method based on a catenary algorithm. Comprising a first server for obtaining original point cloud data collected by an unmanned aerial vehicle; enhancing the original point cloud data; the second server is used for cutting the enhanced data; the second server executes a square grid segmentation algorithm to obtain high point cloud data; the second server executes a DBSCAN clustering algorithm to obtain tower-like object set data, and the second server executes a DenseNet neural network algorithm to obtain electric tower point cloud data; the second server executes a yolov5 neural network